2017
DOI: 10.1016/j.wasman.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of trends in precious metal and copper content of RAM modules in WEEE: Implications for long term recycling potential

Abstract: Precious metal (PM) and copper content of dynamic-RAM modules placed on the market during 1991-2008 has been analysed by AAS following comminution and acid digestion. Linear regression analysis of compositional data ordered according to sample chronology was used to identify historic temporal trends in module composition resulting from changes in manufacturing practices, and to project future trends for use in more accurate assessment of future recycling potential. DRAM was found to be 'high grade' waste with:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 54 publications
0
44
0
5
Order By: Relevance
“…However, previous studies have shown that the amount of copper used in products has changed over time. For some products, such as buildings, cars, and electrical and electronic equipment, the amount of copper is increasing (Charles, Douglas, Hallin, Matthews, & Liversage, 2017). In some cases, it seems likely that copper use will decline as it is replaced by other materials (see below).…”
Section: Copper Intensitymentioning
confidence: 99%
“…However, previous studies have shown that the amount of copper used in products has changed over time. For some products, such as buildings, cars, and electrical and electronic equipment, the amount of copper is increasing (Charles, Douglas, Hallin, Matthews, & Liversage, 2017). In some cases, it seems likely that copper use will decline as it is replaced by other materials (see below).…”
Section: Copper Intensitymentioning
confidence: 99%
“…The dust-like E-waste samples were derived from processed and shredded PCBs. The ESM was ground (using an IKA M20 batch mill, with tungsten carbide blade) to decrease the particle size for more effective acid digestion [23]. The ground ESM particles were sieved to a particle size smaller than 250 µm.…”
Section: Digestion Reagents and Electronic Scrapmentioning
confidence: 99%
“…An efficient recovery of precious metals of PCBs from WEEE is essential to offset demand for primary resources. 17 HF + NaClO mixtures were less performant in this aspect because gold and palladium were brought into a complex leachate as minor components, making their recovery more difficult.…”
Section: Elements Distributionmentioning
confidence: 99%
“…These results are in the range reported in the literature for PCBs from cell phones. 6,7,17,32,[58][59][60] …”
Section: Elements Distributionmentioning
confidence: 99%
See 1 more Smart Citation